Enhancing temperature sensitivity using cyclic polybutylene terephthalate- (c-PBT-) coated fiber bragg grating - Ahmad, H.; Noor, S. F. S. M.; Arusin, A.F.; Samsudin, S. A.; Thambiratnam, K.; Chong, W. Y.; Lim, K. S.; Zulkifli, Mohd Zamani (Hidawi, 2018)
A polybutylene terephthalate (c-PBT) coating for enhancing the temperature sensitivity of a fiber Bragg grating- (FBG-) based sensor is proposed and demonstrated. The coating is seen to increase the sensitivity of the proposed sensor by a factor of approximately 11 times as compared to a bare FBG, giving a Bragg wavelength shift of 0.11 nm/° C with an operating temperature ranging from 30° C to 87° C. The proposed sensor is also easy to fabricate as compared to other similarly coated FBG sensors, giving it a significant advantage for field applications with the added advantage of being easily reformed to fit various housings, making it highly desirable for multiple real-world applications.